(3YeOI GdWGdH aj efGbH Bd CHj WGdHs - (3GHf YfHI , CMeO Hf Ydj Hf MSjf GdOGhOj GdWGdHj GdMSfj, LeGd GdOjf CHh GdYHGS,J (B828 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi Ndb ef GdeGA HTQkG s
(3CNPg GdeDda ef eNJUQ TjNg CHj GdMSf Ydi Hf eMeO Hf GdUhai Ydi GdfSGHI hef JCdjag TjNg CHj fUQ Sgd Hf YHO Gddg GdHNGQi Hbde MajOIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B177 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B6s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B199 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B187 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1167s
Keywords: (3GdJGQjNs